Determinism, moralism, and rationalism - Li, R (2019)
This thesis examines several historical ideas that were prevalent in British intellectual life between the 1920s and 1960s. It regards the philosophy of history not as a theorisation of history, but as an intellectual activity participated in not only by philosophers and theorists, but also historians and literary critics as public intellectuals. Therefore, this thesis is neither a disciplinary study of the ‘philosophy of history’, nor a philosophical treatise that either makes a case for, or repudiates, a Hegelian, metaphysical conception of history. Rather, it is a work of intellectual history that not only seeks to explore how conceptualising the historical process was related to the political, religious, and philosophical contexts during this period, but also attempts to argue that these conceptions of history informed and underpinned many intellectuals’ political views and religious attitudes. Specifically, it tries to investigate several important debates in British intellectual culture over different, and sometimes antagonistic, presuppositions of the meaning and driving force of history. It illustrates the ways in which the relationships between morality and rationality in history were discussed, and argues that disagreements about the nature of history often arose from irreconcilable moral, philosophical and religious standpoints. It also shows that making projections about the future either by drawing historical parallels or by discovering irreversible historical tendencies in the past tended to be accepted by people living in an age that lacks certainty, but it became unacceptable to many when its determinist and teleological implications were underlined.